2007
DOI: 10.1017/s0950268807008424
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective survey of Chikungunya disease in Réunion Island hospital staff

Abstract: Réunion Island (Indian Ocean) has been suffering from its first known Chikungunya virus (CHIKV) epidemic since February 2005. To achieve a better understanding of the disease, a questionnaire was drawn up for hospital staff members and their household. CHIKV infected about one-third of the studied population, the proportion increasing with age and being higher in women. Presence of a garden was associated with CHIKV infection. The geographical distribution of cases was concordant with insect vector Aedes albop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
48
3
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 14 publications
6
48
3
1
Order By: Relevance
“…It has been documented previously that chikungunya outbreaks often follow large rainfall episodes [38][40], which result in a surge in the local mosquito population [41]–[44]. The dominant mosquito population identified in the region during an entomologic assessment performed on March 29-30 was Ae.…”
Section: Methodsmentioning
confidence: 98%
“…It has been documented previously that chikungunya outbreaks often follow large rainfall episodes [38][40], which result in a surge in the local mosquito population [41]–[44]. The dominant mosquito population identified in the region during an entomologic assessment performed on March 29-30 was Ae.…”
Section: Methodsmentioning
confidence: 98%
“…It has been shown that most infected individuals show symptoms, with only ∼5% of cases being asymptomatic 18. Therefore, during an outbreak, presentation with the classical CHIKV disease triad of fever, arthralgia and rash is sufficient to diagnose the condition clinically,19 and, furthermore, there are data to suggest that abrupt presentation with any two of these is sufficient 20. Hence for the purposes of this study, participants were eligible for inclusion if they described an acute illness associated with at least two of these three symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…During the CHIKV outbreak in 2005-07, almost 1.3 million people were affected in 13 states in India [8]. Since 2005, several periodic CHIKV outbreaks were reported in various parts of the world such as in La Réunion Island in the Indian Ocean, Italy, Thailand, China, Congo, Gabon, the Caribbean and the United States (http:// www.cdc.gov/chikungunya/geo/united-states.html) [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%